1998
DOI: 10.1084/jem.188.8.1453
|View full text |Cite
|
Sign up to set email alerts
|

Antigens Varying in Affinity for the B Cell Receptor Induce Differential B Lymphocyte Responses

Abstract: The B cell receptor (BCR) triggers a variety of biological responses that differ depending upon the properties of the antigen. A panel of M13 phage-displayed peptide ligands with varying affinity for the 3-83 antibody was generated to explore the role of antigen-BCR affinity in cell activation studies using primary 3-83 transgenic mouse B cells. Multiple parameters of activation were measured. T cell–independent B cell proliferation, antibody secretion, induction of germline immunoglobulin γ1 transcripts, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
110
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(111 citation statements)
references
References 65 publications
(63 reference statements)
0
110
1
Order By: Relevance
“…Then the activated/memory CD4 ϩ T cells facilitate the activation of CD8 ϩ T cells either through the production of cytokines (20,21) and/or by "conditioning" an APC (probably a DC) through T cell help, which subsequently renders the APC capable of activating CTLs via cognate interactions (7). Additionally, we cannot rule out an effect of B cells secreting cytokines or chemokines (22)(23)(24)(25); although in a milieu of many activated T cells, we doubt that they would be limiting sources of such soluble factors.…”
Section: Discussionmentioning
confidence: 99%
“…Then the activated/memory CD4 ϩ T cells facilitate the activation of CD8 ϩ T cells either through the production of cytokines (20,21) and/or by "conditioning" an APC (probably a DC) through T cell help, which subsequently renders the APC capable of activating CTLs via cognate interactions (7). Additionally, we cannot rule out an effect of B cells secreting cytokines or chemokines (22)(23)(24)(25); although in a milieu of many activated T cells, we doubt that they would be limiting sources of such soluble factors.…”
Section: Discussionmentioning
confidence: 99%
“…This lends credence to our own argument, made above, that differences in the kinetics of Ag association by B cells may variably modulate intracellular signaling. Indeed, in their study, Kouskoff et al have noted that the correlation between response and affinity of BCR for Ag was not perfect (49). They have consequently suggested that, rather than equilibrium affinity, the kinetics of BCR-ligand interaction may constitute the principal determinant of the outcome of activation responses (49).…”
Section: Discussionmentioning
confidence: 99%
“…That the BCR is in fact susceptible to Ag-regulated differential signaling has been recently demonstrated, albeit for T-independent responses (49). Using a panel of M13-phage-displayed peptide ligands with varying affinities for B cells bearing a transgenic sIg receptor, Kouskoff et al (49) reported that BCR-mediated activation, as judged by a variety of parameters, is variably influenced by the affinity of Ag for BCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the apparent similarity of affinity between group I and group II precursors for NPPC may not fully reflect the affinity of group II B cells for the carrier determinants present on the selecting ligand. In addition, the selective forces in vivo are likely to be complex as the B cell receptor is sensitive to binding kinetics (k on and k off ), avidity, and epitope density and organization (47)(48)(49)(50)(51)(52). Clearly, group II Abs develop higher affinity binding for the PC carrier as recurrent mutations can increase the affinity for the PC-protein complex up to 1000-fold greater than T15 (32,53).…”
Section: Why Do T15 Id ϩ B Cells Enter Germinal Centers During the Prmentioning
confidence: 99%